2021
DOI: 10.1177/19322968211035447
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Closed-loop to Manage Gastroparesis in People With Type 1 Diabetes: a Case Series

Abstract: Background: Gastroparesis is associated with unpredictable gastric emptying and can lead to erratic glucose profiles and negative impacts on quality-of-life. Many people with gastroparesis are unable to meet glycemic targets and there is a need for new approaches for this population. Hybrid closed-loop systems improve glucose control and quality-of-life but evidence for their use in people with diabetic gastroparesis is limited. Methods: We present a narrative review of the challenges associated with type 1 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The patients in our study had a suboptimal HbA1c (8.7% ± 2.0), which may be targeted for intervention and subsequent improvement of gastroparesis symptoms. Recent studies of hybrid closed loop in patients with type 1 diabetes and gastroparesis have been promising 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients in our study had a suboptimal HbA1c (8.7% ± 2.0), which may be targeted for intervention and subsequent improvement of gastroparesis symptoms. Recent studies of hybrid closed loop in patients with type 1 diabetes and gastroparesis have been promising 19 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of hybrid closed loop in patients with type 1 diabetes and gastroparesis have been promising. 19 We identified significant, underrecognised malnutrition in this group, and only half were assessed by a dietitian. Nutrition is a pillar of gastroparesis management, and suspicion of gastroparesis should prompt a dietitian referral.…”
Section: Discussionmentioning
confidence: 99%
“…In the presented case, we decided to start continuous subcutaneous insulin infusion therapy with an aHCL system. Two studies have already demonstrated the efficacy of HCL systems in adults with T1D and gastroparesis ( 26 , 27 ). In particular, Daly et al ( 26 ) recently reported significant reductions in HbA1c and mean glucose in five patients over one year of HCL use, while Kaur et al ( 27 ) had previously shown that HCL had similar effectiveness and safety in adults with T1D and gastroparesis compared to age, sex, and diabetes duration controls.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of improvement in chronic glycaemic control (HbA 1c ) remains uncertain with an absence of controlled studies, although a prospective study reported normalisation of delayed gastric emptying, measured with scintigraphy, following improved glycaemic control [ 66 ]. A small trial in individuals with type 1 diabetes and gastroparesis found that hybrid closed loop insulin pump therapy improved the mean percentage time that blood glucose was in range (3.9–10 mmol/l) from 26% to 58.4%, however neither gastrointestinal symptoms nor gastric emptying were evaluated [ 67 ]. Nutritional support (e.g.…”
Section: Management Of Gastroparesis Associated With Upper Gastrointe...mentioning
confidence: 99%